KECERIAAN ANAK-ANAK DALAM BERMAINSEBAGAI SUMBER IDE PENCIPTAAN KARYA SENI LUKIS - Kim Myung Hee Myung Hee; Amir Gozali (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
The creation of the painting in this final project was inspired by the life of the artist's family who believed that the joy of children was important in giving a positive impact on their lives. Happiness is the right of every human being, including children, regardless of their family background and the problems they are facing. The joy of children while playing is the main concern and is used as an idea in the creation of paintings. While the expression of the joy of children when playing, interacting, and socializing among them in the open is a concept that will be offered in this painting, with the hope that it can be a place to express ideas as well as be a lesson about the importance of having fun for children from an early age. The artist uses a method consisting of several stages, namely observation, incubation, documentation, and others. In its realization, several processes are carried out, namely making sketches of shapes, color blocking, working on details, finishing touches, and then packaging presentations to be presented in the form of exhibitions.